Kinetic and Thermodynamic Studies on the Adsorption of Reactive Red 239 by Carra Sawdust Treated with Formaldehyde - Nedher Sanchez; Tânia M. Benedetti; Mario Vazquez; Susana I. Córdoba de Torresi; Roberto M. Torresi (Adsorption Science & Technology)
In this study, carra sawdust pre-treated with formaldehyde was used to adsorb reactive red 239 (RR239). The effects of several experimental conditions, including the concentration of dye, sorbent dosage, temperature, ionic strength, stirring speed and solution pH, on the kinetics of the adsorption process have been studied, and the experimental data were fitted to pseudo-second-order model. A study of the intra-particle diffusion model indicates that the mechanism of dye adsorption using carra sawdust is rather complex and is most likely a combination of external mass transfer and intra-particle diffusion. The experimental data obtained at equilibrium were analyzed using the Langmuir and Freundlich isotherm models, and the results indicated that at this concentration range, both models can be applied for obtaining the equilibrium parameters. The maximum dye uptake obtained at 298 K was found to be 15.1 mg g −1 . In contrast to the usual systems, the reactive dye studied in the present work is strongly attached to the sawdust even after several washes with water, allowing it to be discarded as a solid waste.